Eating behavior patterns in relation to obesity phenotypes and beige adipose tissue content with a focus on young women; a narrative review - Walkiewicz, Katarzyna W.; Dzięgielewska-Gęsiak, Sylwia; Myrcik, Dariusz; Bednarczyk, Martyna; Muc-Wierzgoń, Małgorzata (Frontiers in Nutrition, 2025)
Eating behaviors extend beyond the physiological satisfaction of hunger; they play a key role in emotion regulation, reward mechanisms, and environmental adaptation. Stable patterns of thoughts, emotions, and food choices create eating styles—complex, individualized behavioral constructs shaped partly by genetic predisposition (e.g., genes influencing food preferences) and partly by family, social, and personality factors. Eating styles are an important determinant of the risk of eating disorders, obesity, and associated metabolic complications. The literature distinguishes adaptive and maladaptive (problematic) styles, which differ in their effects on body weight regulation and health behaviors. Obesity itself is not a homogeneous clinical entity but rather a spectrum of phenotypes differing in adipose tissue distribution (visceral vs. subcutaneous), the severity of metabolic disturbances, and the biological activity of adipocytes. Increasing attention has been paid to the functional diversity of adipose tissue, particularly beige adipose tissue (BeAT), which—through thermogenesis and glucose regulation—is increasingly recognized as a protective factor against insulin resistance and metabolic syndrome. Its activity is highly variable and may be influenced by behavioral factors, including eating patterns. This review aims to summarize current evidence on the relationship between eating styles, obesity phenotypes, and the role of beige adipose tissue. The analysis focuses on young women (<25 years), a group undergoing dynamic hormonal changes and at high risk of establishing persistent eating habits. By integrating psychological and biological determinants of obesity, this paper proposes a conceptual framework linking eating styles, adipose tissue distribution, and metabolic activity—with particular emphasis on BeAT—as a potential target for early prevention of metabolic disorders.